Fourth IIGS International Conference on the Muslim World - Shujaat A. Khan (International Institute of Islamic Thought, 1996)
The Fourth International Conference on the Muslim World, organized by the International Islamic Geographic Society, was hosted by Al al-Bayt University, Amman, Jordan. This four-day conference brought together a distinguished international gathering of geographers and social scientists to discuss issues of concern to Muslim countries. The conference was held in a very pleasant, cordial, and hospitable environment, and the excursion trip at its end, which provided an opportunity to visit historical places and archaeological sites, made it all the more enjoyable and memorable. The conference was comprised of five regular sessions and featured sixteen presentations before a select audience of no more than fifty individuals. Mohammad Adnan Al-Bakhit, president of Al al-Bayt University, gave the welcoming address. He greeted the participants wannly and expressed the hope that this conference would promote research and motivate young Muslim geographers to undertake scholarly pursuits. He said that the university is committed to promoting scientific research, with an Islamic outlook, in all fields of knowledge. Mushtaqur Rehman, IIGS secretary and prominent Muslim geographer and anthropologist, pronounced the conference's theme, highlighted its multidisciplinary dimensions, and elaborated on its significance to the Muslim world, which has serious developmental problems. The first session, chaired by Rehman, started with Hussain A. Amery's insightful examination of water management in the geopolitical context of the Middle East. He emphasized the need for cooperation among the region's Muslim states and the use of new technologies for harvesting water and treating waste water for reuse. A. R. Hamideh focused on the issue of population growth in Muslim countries and refuted categorically the argument of Western anthropologists that the Islamic value system is a major obstacle in dealing with demographic issues. Session two was chaired by Hani D. Tabba and featured three presentations. A. Hussain examined the nation-state in a historical perspective aRd argued that unless Muslim countries abandon this structure, they will be unable to establish an Islamic Common Market and will not achieve economic development. Abdel Bagi investigated the socioeconomic problems of rural-urban migration, largely due to desertification, in Sudan. He suggested the formulation of policies designed to revitalize the rural economy 422 and thereby reverse this migration. Salman Abu Settah examined the Palestinian Holocaust of 1984 and deplored the media’s efforts to keep the Jewish Holocaust alive while largely ignoring Palestinian massacres, suffering, and humiliation which has been forgotten by the world. Rasheed Al- Feel discussed Muslim problems in a geographical context and concluded that they could be molved by mobilizing resources and promoting inter- Muslim trade. Session three was chaired by Omar Shadaifat and included two presentations. Rue1 Hanks gave an objective assessment of Uzbekistan’s contemporary sociopolitical environment and concluded that the present Islamist-secular confrontation will soon end, marking a clear victory for those committed deeply to an Islamic way of life. Ahmad Agala examined Jordan’s political system and observed that popular participation in Jordan is far higher than in many Muslim republics. Yaser M. Najjar evaluated Jordan’s development planning and remarked that a capital-poor country like Jordan cannot achieve industrialization without borrowing high-cost capital and technology from abroad. He suggested that economic cooperation among Muslim countries could help resolve the problem of capital scarcity. S. Ali Khan investigated the process of development from the capitalist and Islamic perspectives. He pointed out that material well-being is capitalism’s only goal, whereas the Islamic approach stresses the realization of both material and spiritual well-being. He also stated that the realization of both goals is possible only through restructuring the existing political and economic institutions within the context of an Islamic social order ...